(3ehWF GdehWCs - (3eMeO jf jMji Hf Sdjeg GdjhfSj,J (B1354 (3g` s ((3eMeO Hf CMeO Hf CHj HcQ Hf YTGi s)
(3ChdgG (B:s
(3CeG HYO aGdZQV ef gPG GdcJGH GdeHGQc GNJUGQ ehWC GdEeGe eGdc Hf CfS HGdGcJaGA HGdeJf Yf GdESfGA hHMPa McGjGJ GdCMhGd EdG dfcJg JbJVi GdMcGjI s
(3BNQgG (B:s
(3eG LGA ai CSeGA GdfHi Udi Gddg Ydjg hSde , bGd QShd Gddg di NeSI CSeGA (B: (3CfG eMeO , hCfGCMeO , hCfG GdeGLi GdPi jeMh Gddg Hg GdcaQ , hCfG dMGTQ hCfG GdYGbH Je s
(3HgG fXGe GdJYbjHIs
(3fSNI LjOI JGeIs
(3HYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs